After Crisis Scenarios for CEECs: A simulation through the MASST3 model - Roberta Capello; Andrea Caragliu (European Regional Science Association (ERSA), 2014)
Over the last few years, the world economy has gone through a severe period of economic downturn, the worst since the end of WWII. Although the crisis has been widely covered on the media, less common knowledge is the fact that the crisis has engendered responses in the economic systems, in the form of structural adjustments. The aim of the present paper is to build after-crisis scenarios in order to raise awareness on the possible ways out of the present economic downturn. The scenarios that will be presented in the paper are "response to the crisis scenarios", in that built on the basis of alternative trends that structural adjustments can follow. In particular, the paper presents a reference scenario, whereby the first structural changes that have been caused by the crisis, as well as the early structural reactions that can be already observed in the data, are modeled. This scenario represents the benchmark against which the two alternative scenarios, based on assuming radically different trends in the evolution of the responses to the crisis, will be compared. In particular, a first scenario is the so called regional cohesion scenario, a scenario of competitiveness obtained thanks to the exploitation of local excellence and untapped local resources. In this scenario, economic resources, in particular innovation-related and FDI-driven, are assumed to be distributed more evenly with respect to the reference scenario, thus shifting towards areas hosting second-rank cities. The second alternative scenario is a social cohesion scenario, built around the idea of limiting social costs of the crisis. In this second alternative scenario, resources are assumed to be distributed differently with respect to both the reference and the regional cohesion scenario, and in particular to be oriented towards less urbanized areas. Both scenarios have positive and shareable reasons to be developed, and have therefore the same legitimization to be supported by policy-makers. In other words, neither is to be considered ex-ante preferable, and both can be justified on the basis of different policy targets. The results of the simulation exercise, obtained by running the macroeconomic regional growth forecasting model MASST3, are rather interesting. Unexpectedly, the regional cohesion scenario achieves both the highest aggregate growth rates, as well as the lowest increase in regional disparities. Contrary to general beliefs, the social cohesion scenario displays less effectiveness in fostering convergence processes. These results may drive future cohesion policies to reinforce local excellence and tap the untapped resources.
Keywords: R11; R15; 330; Economic way out of the crisis; simulation; regional growth; quantitative foresight (and)